FLAVONOIDS AND PHENOLIC CONTENT IN WHEAT GRASS PLANT (TRITICUM AESTIVUM). - Zendehbad, Seyed Hossein; Mehran, Mohammad Javad; Malla, Sudhakar (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The study was mainly designed to screen various solvent extracts of the leaves of wheatgrass (Triticum aestivum) to show the potent antioxidant activity in order to find possible sources for novel antioxidants in food and pharmaceutical supplements. A detailed study was performed on the antioxidant activity of the methanol extract and chloroform extract of T. aestivum. The fractions were initially screened for the phenolics and flavonoids and then estimated for the total polyphenols and the flavonoids. Further, the fractions were used for showing the potential antioxidant activity. The antioxidant activity was displayed by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity and H2O2 scavenging activity. The plant responded positive for both the phytochemicals screened. The total phenolic content was found to be more for methanol fraction (44%) when compared with the chloroform fraction (12%). The total flavonoids were more for the chloroform fraction (40.420 ± 0.13 μg/mL) when compared with the methanol fraction (22.873 ± 0.05). Methanol fraction was shown to contain more polyphenols (44%), than the methanol fraction (12%). Methanol fraction displayed strong DPPH scavenging activity (IC50 4.258 ± 0.54 minute) in reference to the positive control ascorbic acid exhibited 3.3266 ± 0.38 minute. The scavenging activities of the chloroform fraction were (IC50 5.217 ± 0.52 minute). The scavenging activity for hydrogen peroxide of various solvent extracts from Wheatgrass was in the order of positive control > methanol > chloroform respectively. The data from H2O2 activity showed that the activity was dose-dependent. The H2O2 activity at a concentration of 200 μg/mL was found to 57.11%, 71.13%, and 86.54% for the chloroform, methanol, and positive control fractions, respectively. Keywords: Triticum aestivum, Total phenolics, 2,2-diphenyl-1-picrylhydrazyl, Antioxidant, H2O2 scavenging activity.